EFFECT OF RISPERIDONE ON HEART RATE DYNAMICS OF PATIENTS HAVING SCHIZOPHRENIA - AMJAD, N; HAQ, MIU; KHAN, AR; AHMED, R; NAVEED, S (Biological and Clinical Sciences Research Journal, 2022)
Risperidone is a first-line antipsychotic drug for treating schizophrenia. It has antiadrenergic action but vhas a negligible impact on neurocardiac regulation. However, due to the relationship between cardiac autonomic regulation and a psychotic state, risperidone induces treatment-associated changes in heart rate variability (HRV). This Prospective study was designed to assess the effect of risperidone therapy on the heart rate dynamics of schizophrenic patients. Psychiatry & Medicine Department, Nishtar Medical Hospital, conducted this study from January 2021 to January 2022. After screening, patients with psychosis causing psychosocial impairment (PANSS score 70) were included in the study. Fifteen patients were selected after the screening. All were administered risperidone. A Control group having age and gender-matched subjects was selected, and ECG was done. Data from 15 controls and 15 patients were analyzed. Clinical Global Impressions-Severity of illness scale (CGI-S) and Positive and Negative Syndrome Scale (PANSS) were used for quantifying psychiatric symptoms. Drug-Induced Extrapyramidal Symptoms Scale (DIEPSS) was used to measure drug-associated movement disorders. The mean risperidone dose was 3.2± 0.8 mg/ day. Data collected after 6 weeks of treatment showed that the mean PANSS score, positive symptoms subscale score, negative symptoms subscale score, CGI-S score and general psychopathology score decreased significantly (p< 0.001). Comparison of HRV parameters between the control group (healthy subjects) and unmedicated patients showed a significant group effect (p<0.001). Evaluation of the association between the severity of psychotic symptoms and HRV measures shows the negative correlation between PANSS positive symptoms score changes and SDNN changes (p= .012).Risperidone treatment in acutely ill schizophrenic patients leads to an increase in cardio-vagal activity, thus causing improvement in sympathovagal imbalance.